Sydpolekspedisjoner (Polarboken, 1994)
Keywords: Antarktis; ekspedisjoner

Teltet på Sydpolen - Dannevig, Alv (Vær & klima, 1994)
Keywords: Antarktis; ekspedisjoner; logistikk

Water mass distribution and tides along the Filchner-Ronne ice shelf: preleminary [sic] results from the Norwegian Antarctic Expedition 1992/93 - Gammelsrød, Tor (Filchner-Ronne Ice Shelf Programme. Report, 1994)
Keywords: Sørishavet; oseanografi

Synedropsis gen. nov., a genus of araphid diatoms associated with sea ice - Hasle, Grethe Rytter; Medlin, Linda K.; Syvertsen, Erik E. (Phycologia, 1994)
A new araphid diatom genus, Synedropsis Hasle, Medlin et Syvertsen, is described from sea ice. The generitype, Synedropsis hyperborea (Grunow) Hasle, Medlin et Syvertsen from the Arctic, was first described as a species of Synedra, as was the antarctic Synedropsis fragilis (Manguin) Hasle, Syvertsen et Medlin. A second antarctic species of Synedropsis is a new combination of Cymatosira laevis Heiden in Heiden & Kolbe. In addition four new taxa, S. hyperboreoides Hasle, Syvertsen et Medlin, S. recta Hasle, Medlin et Syvertsen, S. lata Hasle, Medlin et Syvertsen and S. lata var. angustata Hasle, Medlin et Syvertsen are described from the Antarctic. The valve wall is laminar with uniseriate, often poorly developed striae and a wide sternum. Each valve possesses apical fields composed of slits. A labiate process is positioned near one apical slit field. The valve outline for most species exhibits considerable stadial variation. The girdle has several bands, most with one row of poroids close to the pars interior. Thus Synedropsis is closely related to the marine Fragilaria striatula Lyngbye except in the structure of the apical fields and the number of bands. Species observed in uncleaned material appeared in stellate or, more seldom, ribbon-shaped colonies. Synedropsis hyperborea is a common epiphyte on the ice-associated Melosira arctica Dickie in the Arctic. The antarctic species were found mainly in the bottom ice community, S. fragilis as an epiphyte on other diatoms.
Keywords: Rosshavet; Sørishavet; Weddellhavet; botanikk; diatomeer; havis; kiselalger; marin biologi; plankton

High resolution climatic information from short firn cores, western Dronning Maud Land, Antarctica - Isaksson, Elisabeth; Karlén, Wibjörn (Climatic Change, 1994)
In this paper a detailed record of major ions from a 20 m deep firn core from Amundsenisen, western Dronning Maud Land, Antarctica, is presented. The core was drilled at 75° S, 2° E (2900 m a.s.l.) during austral summer 1991/92. The following ions were measured at 3 cm resolution: Na+, Mg2+, Ca2+, Cl−, NO3−, S04 2− and CH3SO3H (MSA). The core was dated back to 1865 using a combination of chemical records and volcanic reference horizons. The volcanic eruptions identified in this core are Mount Ngauruhoe, New Zealand (1974–75), Mount Agung, Indonesia (1963), Azul, Argentina (1932), and a broad peak that corresponds in time toTarawera, New Zealand (1886), Falcon Island, South Shetlands, Southern Ocean (1885), and Krakatau, Indonesia (1883). There are no trends in any of the ion records, but the annual to decadal changes are large. The mean concentrations of the measured ions are in agreement with those from other high-altitude cores from the Antarctic plateau. At this core site there may be a correspondence between peaks in the MSA record and major El Niño–Southern Oscillation events.
Keywords: Dronning Maud Land; glasiologi; kjemi; klima

Spatial and temporal patterns in snow accumulation, western Dronning Maud Land, Antarctica - Isaksson, Elisabeth; Karlén, Wibjörn (Journal of Glaciology, 1994)
During the Swedish Antarctic Expedition to Dronning Maud Land, Antarctica, 1988–89 the net accumulation was estimated for an area from the coast to about 400 km inland. Stake measurements were used to obtain the spatial variability and firn cores were used for the temporal variability. The mean annual accumulation for the period 1976–88 is about 0.4mw.e. for Riiser-Larsenisen and about 0.3mw.e. for the area above the grounding line. The accumulation rate at higher altitudes, > 2500 m a.s.1., is about 0.1 m w.e. for 1955–88. One record from the ice shelf covers the period 1957–88, and suggests an increase in accumulation of about 12%. Between 1976 and 1988, the accumulation has decreased by about 50%, most likely due to lower temperatures as suggested by the temperature record from Halley.
Keywords: Dronning Maud Land; glasiologi

Alene til Sydpolen - Kagge, Erling (Polarboken, 1994)
Keywords: Antarktis; ekspedisjoner

Antarktis - den siste villmark - Lorentsen, Svein-Håkon (NINA-Nytt, 1994)
Keywords: Dronning Maud Land; ekspedisjoner; forskning

Sex determination of Antarctic Petrels Thalassoica antarctica by discriminant analysis of morphometric characters - Lorentsen, Svein-Håkon; Røv, Nils (Polar Biology, 1994)
We present data on sexual dimorphism in some morphological measurements (wing length, head length, bill depth and bill length) in the Antarctic Petrel Thalassoica antarctica. Males were on average larger than females for all measurements. Sexual dimorphism was on average largest for bill depths whereas wing lengths discriminated least between the sexes. A discriminant function including bill depth, head length and wing length correctly sexed 92% of the sample. Due to between-measurer variation it is recommended that morphometric measurements obtained by others on sexed birds are compared with ours before proceeding with the use of the discriminant function on unsexed individuals.
Keywords: Dronning Maud Land; NARE 1991/92; biodiversitet; fugler; ornitologi; zoologi; økologi

Digestibility of krill (Euphausia superba and Thysanoessa sp.) in minke whales (Balaenoptera acutorostrata) and crabeater seals (Lobodon carcinophagus) - Mårtensson, Per-Erik; Nordøy, Erling S; Blix, Arnoldus Schytte (British Journal of Nutrition, 1994)
Keywords: Dronning Maud Land; forskning; hvaler; krill; plankton; seler; zoologi

A bibliography of terrestrial biological research in Dronning Maud Land, Antarctica - Newton, I P; Cooper, J; Mehlum, Fridtjof; Thor, Göran (South African Journal of Antarctic Research, 1994)
A bibliography of terrestrial biological research in Dronning Maud Land, Antarctica, of 388 titles from 1954 to 1994 is provided as an aid to researchers working in the region.
Keywords: Dronning Maud Land; bibliografi; biologi

A model of ice shelf-ocean interaction with application to the Filchner-Ronne and Ross Ice Shelves - Nøst, Ole Anders; Foldvik, Arne (Journal of Geophysical Research: Oceans, 1994)
A simple analytical model has been developed to study the formation of Ice Shelf Water (ISW). ISW is assumed to flow as a buoyancy-driven layer underneath the ice shelf. A relation between potential temperature and salinity in the ISW layer is calculated from the mass and energy balance. This temperature-salinity relation is shown to depend only on the temperature and the salinity of the source water mass and to be practically independent of entrainment and melt rates. The model results are obtained without making any assumptions about entrainment and melt rates. The model is in good agreement with observations under the Ronne Ice Shelf, and it indicates that ISW in the Filchner Depression is formed from Western Shelf Water (WSW) with salinity higher than 34.75 practical salinity units. Such high-salinity water is only observed in the Ronne Depression in the western part of the continental shelf. This implies a circulation of WSW, under the Filchner-Ronne Ice Shelf, from the Ronne Depression into the Filchner Depression. Similarly, the model shows that the ISW observed under J9 at the Ross Ice Shelf has been formed from Low Salinity Shelf Water (LSSW) from the eastern parts of the Ross Sea continental shelf. LSSW must therefore circulate under the eastern parts of the Ross Ice Shelf.
Keywords: Antarktis; geofysikk; isshelf; kontinentalsokkel; oseanografi

Occurrence of Pseudoterranova decipiens (Nematoda) in fish from the Southeastern Weddell Sea (Antarctic) - Palm, Harry; Andersen, Karin; Klöser, Heinz; Plötz, Joachim (Polar Biology, 1994)
Eleven fish species from the Weddell Sea (Antarctic) were examined for infestation with anisakid nematodes. Two species of the genus Contracaecum and the sealworm Pseudoterranova decipiens were isolated from the liver and the body cavity of fish affected. Only two specimens of P. decipiens (1.4%) partly invaded the belly flaps. The following fish species were infested by P. decipiens at the given prevalences: Cygnodraco mawsoni (74.4%), Trematomus scotti (23.2%), Pagetopsis maculatus (10.0%), Cryodraco antarcticus (7.1%), Trematomus lepidorhinus (3.0%), and Dolloidraco longedorsalis (2.7%). All of these, except Trematomus scotti, are new host records. Chaenodraco wilsoni, Chionodraco myersi, Gerlachea australis, Racovitzia glacialis and T. eulepidotus were not infested. The reasons for low prevalence and intensity of infestation are seen in the difficulties of P. decipiens in completing its benthic life cycle in the Weddell Sea environment, in the absence of shallow coastal waters due to the floating shelf-ice. Cygnodraco mawsoni is a crucial intermediate host, without which completion of the parasite life cycle might not be possible. In order to clarify the taxonomical position of Antarctic Pseudoterranova, morphological comparisons with specimens of P. decipiens from the German and Norwegian coast were made using scanning electron microscopy. Results revealed no differences; hence, all specimens studied belong to the same species P. decipiens.
Keywords: Sørishavet; Weddellhavet; biodiversitet; fisker; marin biologi; økologi

Rock mapping of glaciated areas by satellite image processing - Salvini, Francesco; Della Maggiore, Roberto; Fortunati, Luciano; Mazzarini, Francesco (Polar Research, 1994)
Keywords: Antarktis; geologi; polarområdene; satellitt bilder

Solorina Spongiosa in Antarctica: An Extremely Disjunct Bipolar Lichen - Smith, R. I. Lewis; Øvstedal, Dag Olav (The Lichenologist, 1994)
The bipolar foliose lichen Solorina spongiosa (Sm.) Anzi is reported from James Ross Island, Antarctica, where it grows on moss. This is only the third known occurrence of this lichen from the Southern Hemisphere, the other localities being in Tierra del Fuego and New Zealand. Its morphology resembles that of the New Zealand population and arctic-alpine populations from the Northern Hemisphere, although there are some differences in apothecial and spore size. As elsewhere, it occupies base-rich habitats colonized by predominantly calcicolous mosses and lichens.
Keywords: Antarktis; botanikk; lav; moser; planter

The Antarctic Treaty system and Antarctic tourism: towards a legal regime? - Vidas, Davor (International Challenges, 1994)
Keywords: Antarktis; jus; turisme

Spectral bi-directional reflectance of snow and glacier ice measured in Dronning Maud Land, Antarctica - Winther, Jan-Gunnar (Annals of Glaciology, 1994)
Visible and near-infrared spectral reflectances of snow and superimposed ice were measured in Dronning Maud Land, Antarctica, during the 1992-93 austral summer. Spectral-reflectance curves of both snow and superimposed ice remain high ( > 80%) in the visible region. A pronounced decrease in reflectance appears in the near-infrared, especially for superimposed ice. Superimposed ice with a 1 cm thick surface layer of ice-bound snow crystals had a considerably higher reflectance than superimposed ice containing only a few snow crystals. Furthermore, these data prove that snow and superimposed ice reflect solar radiation specularly and suggest that the anisotropy strengthens with increasing wavelengths. Integrated in-situ reflectances corresponding to Landsat TM bands 1-4 show that TM band 1 is least affected, whereas TM band 4 is most affected by anisotropy. Furthermore, the anisotropy increases with increasing off-nadir viewing angles up to an angle corresponding to 90°-θs (θs = solar elevation). For a 15° off-nadir sensor-observation angle, the average snow reflectance for TM bands 1--4 is about 10% higher than at nadir. Similarly, the apparent reflectance can be more than 50% higher than the nadir reflectance for larger observation angles. Consequently, if satellite-derived reflectances are going to be considered as absolute values, a topographic-correction model is needed to correct for the effects of anisotropy.
Keywords: Dronning Maud Land; glasiologi